Transdisciplinarni pristup u razmatranju odnosa znanost - teologija - Cerovac, Krešimir (Array, 2019)
There are many reasons why a partnership dialogue between theology (religion) and the natural sciences is needed. However, first and foremost this must be a conversation between one human being and another regarding the most important of human interests. The most effective way to approach complex issues and problems in the dialogue between theology and science is the transdisciplinary approach. Transdisciplinarity can solve prob lems which cannot be resolved by separate attempts. This approach can connect different modes of thought, that is, thought beginning with different points of view on the material world or religion. The transdisciplinary approach takes on the role of mediator, which demands at the “round table” that which unites human beings on a universal human level. This is a new, challenging and demanding approach which requires researchers to leave their own field of interest and strive to learn about other fields. The transdisciplinary approach, as “critical rationality” and a new way of thinking, opposed to classical and reductive rationalism, emphasizing objectivity, is based on controlled conflict–induced paradoxes. Transdisciplinarity creates a new quality — which is not an arithmetic sum of individual disciplines — and enables articulation, i.e. a link between two, at first glance, controversial disciplinary modes of thought.